PENGARUH FAKTOR SITUASIONAL DAN FAKTOR KARAKTERISTIK PERSONAL AUDITOR TERHADAP PREMATURE SIGN OFF (Studi Empiris Pada Kantor Akuntan Publik Pekanbaru, Padang dan Palembang) - Akbari, Akhirumi Zakiah; DP, Emrinaldi Nur; Hariyani, Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research are to analyze time pressure, audit risk, review procedures and quality control, materiality, locus of control, self esteem in relation to ambition and auditor turn over intention that can affect the premature sign off. The population was all the independent auditor who worked at the KAP in the city of Pekanbaru, Padang and Palembang. While the sample of this research in the KAP auditors work in Pekanbaru, Padang and Palembang with 82 sample auditors. Methods of data collection in this study is a survey method with a questionnaire instrument. Method of data analysis used to test the quality of the data that include validity, reliability testing, and hypothesis testing is the analysis of the multiple linear regression using software SmartPLS Version2 M3. Hypothesis testing using partial least square test showed that the variables time pressure, audit risk, review procedures and quality control, materiality and locus of control significantly influence the premature sign off. While the variable self esteem in relation to ambition and auditor turn over intention does not directly affect the premature sign off. Value of R-Square indicates that the variables jointly time pressure, audit risk, review procedures and quality control, materiality, locus of control, self esteem in relation to ambition and auditor turn over intention contribute to the dependent variable (premature sign off) of 44.8%, while the remaining 55.2% is explained by other variables outside the research model.Keywords: premature sign off, situational factor and personal characteristic factor auditors